Holocene range collapse of giant muntjacs and pseudo‐endemism in the Annamite large mammal fauna. (18th May 2016) - Turvey, Samuel T.; Hansford, James; Brace, Selina; Mullin, Victoria; Gu, Shengxiao; Sun, Guoping
Abstract: Aim: To clarify the post‐glacial biogeography of the Annamite and eastern Chinese ungulate faunas, and determine whether current understanding of Asian mammalian biogeography is biased by pseudo‐extinctions and pseudo‐endemism associated with a historical extinction filter. Location: Modern‐day specimens of giant muntjac ( Muntiacus vuquangensis ) from the Annamite Mountains of Laos and Vietnam were compared with zooarchaeological specimens of extinct giant muntjac ( M. gigas ) from eastern China, and with a reference sample of northern red muntjac ( M. vaginalis ) from China, Southeast Asia and South Asia. Methods: We analysed a data set of antler measurements using Multivariate analyses of variance (MANOVAs), principal component analyses (PCAs) and scaling relationships, to quantify morphometric variation between extinct and living giant muntjacs in relation to variation shown by a different sympatric large‐bodied muntjac species. We also attempted ancient biomolecule analysis of Holocene samples from China. Results: Although the combined giant muntjac sample can be differentiated from the reference red muntjac sample in all of our multivariate morphometric analyses, no significant differences are shown between extinct and living giant muntjacs using any analyses, matching the pattern seen when comparing conspecific red muntjac samples from across the same geographical region. Main conclusions: We find no support for recognizing extinct and living giant muntjacs as distinct taxa, and post‐glacial populations from China and the Annamites should probably all be referred to M. gigas . The likely conspecificity of giant muntjacs across Eastern and Southeast Asia demonstrates that current‐day Asian mammalian biogeography has been shaped by an extinction filter and challenges the idea that the Annamite region represents a cradle of evolution; instead, it may represent a refuge of diversity for some taxa, preserving remnant pseudo‐endemic populations of species that have been extirpated across other parts of their former ranges.